3.A. Workshop: Integrating the use of genomic data in personalised healthcare: implications across the board. (20th October 2021) - ,; ,
Abstract:  : Genomics has the potential to benefit overall health by ensuring that citizens and patients receive timely and effective diagnosis, information, and treatment. Much progress has been made in genetic risk assessment for a wide variety of conditions, with implications for implementation of personalized medicine (PM). PM strategies include the use of decision-making processes based on biomarker-driven approaches that may have the desired discriminatory accuracy to distinguish between high-risk and low-risk subjects and may guide prevention strategies, prophylactic and therapeutic decisions. Many countries in Europe have nascent PM programmes, and human genomics is undergoing a step change from being a predominantly research-driven activity to one driven through healthcare. However, for any healthcare system, the integration of genomic data for PM requires extensive adjustments. These adjustments include, the development of technical infrastructure, competences and ethical legal social implications frameworks, for acquiring, storing, sharing, interpreting and delivering genomic information. This workshop will discuss how the access to genomic and linked phenotypic data at population-scale has tremendous potential to effectively advance PM in healthcare systems, but to fully realise this ambition, it is crucial that a genome and health data-sharing framework is developed and can effectively reach healthcare systems in European Member States and beyond. Key messages: The adoption of genomics by European healthcare systems is crucial to fulfill the potential of Personalised Medicine for patients and citizens. Effective data sharing agreements are needed, because without them the personalised healthcare approach will not work.